Reducing the Use of Diuron-Active Herbicides Using a Combination of Wood Vinegar from Lignocellulosic Waste in Pineapple Plantations - Yosua Pratama Simangunsong; Herdhata Agusta; Mochamad Hasjim Bintoro Djoefrie (Journal of Tropical Crop Science, 2026)
Pineapple waste, which is rich in lignocellulosic compounds, can be thermally converted into environmentally friendly bioherbicides. This study aimed to evaluate the potential of lignin-derived compounds from lignocellulosic waste as a bioherbicide and to identify an effective formulation for reducing the use of diuron-based herbicides in pineapple plantations. Pyrolysis was conducted at subcritical temperatures, and the resulting wood vinegar was analyzed by GC MS to identify phenolic compounds. Pyrolysis at 250–300 °C produced phenolic compounds accounting for 40.20% of the chromatogram area, while pyrolysis at 400–450 °C produced 49.61%. The efficacy test included several treatments: pyrolysis products from 400–450 °C at 5% and 10%, pyrolysis products from 250 350 °C at 5% and 10%, diuron herbicide at 0.5 g/L, combinations of herbicide with two selected pyrolysis products, and a standard diuron application as the control. The results showed that wood vinegar produced at 400–450 °C and applied at 10% could suppress seed bank germination, with an effectiveness comparable to that of diuron at 0.5 g/L. This wood vinegar formulation was then used in a second efficacy test under pineapple cultivation conditions to assess whether diuron use could be reduced when combined with wood vinegar. The results indicated that combining 70% herbicide with 10% wood vinegar suppressed weed growth to a level similar to the 100% herbicide standard treatment. This study may serve as a reference for reducing the use of synthetic herbicides in pineapple cultivation.